Risk attitudes and affective states among young adults - Raziya, Anzisca (School of Economics, 2025)
This study examines how negative emotions influence risk attitudes and chance attitudes profiles among young adults using data from a novel behaviour modification programme targeted at young adults in South Africa. Risk attitudes are estimated structurally by assuming a stan-dard power utility function for the risky prospects they face in the risk elicitation experiment. The power parameter is recovered, and checks are performed for evidence of risk aversion and probability distortions. We find that while both the control and treatment groups exhibit risk aversion, the programme does not significantly alter risk aversion overall. However, significant treatment effects emerge with respect to probability distortion, suggesting that the programme fosters behaviour more closely aligned with expected utility maximisation. The programme appears to decrease the likelihood that individuals never experience anger or hostility. However, the effects on anger and hostility do not account for the observed treatment effects on probability distortions. Furthermore, individuals who never experience nervousness tend towards risk neutrality, while those who experience it are typically risk averse. Interestingly, both nervousness and fear correlate negatively with probability distortions, indicating a more pessimistic approach to risk among those who do not experience these emotions. This pattern holds across both the treatment and control groups, suggesting that these emotions remain relatively stable in the programme context. These findings emphasise the importance of considering affective states in designing interventions to address risky behaviours among young adults, contributing to improved public health outcomes.